Problems of Students in The Translation of Arabic into Indonesian in the Translation Lesson for Students of The Twelfth semester at The Islamic Boarding School Koto, Petai, Kerinci, Jambi - Muhammad Fadhlan (Educan : Jurnal Pendidikan Islam, 2019)
Al-muhsinin Al-islami boarding school is one of the educational institutions under the supervision of the Ministry of religion. The material contained in the Arabic language learning curriculum in sets them down. As nahwu science, neuroscience, science of tasawwuf and more. As for the lesson of the translations is one of the lessons of the curriculum the cottage it self in order to enhance the students in understanding the Arabic especially the books of turast. Almuhsinin boarding schools implement learning method in translation in Arabic. Students learn books of the turast defined by the method (Qowaid-Wa tarjamah) or methods and rules translations. The type of research used researchers to find the problem is with the way research studies field with a discussion of qualitative analysis deskriktif. To get the necessary data, the authors use a method of observation, Interview and documentation, and for managing the data so as to achieve a perfect conclusion, the author uses descriptive analysis methods, Miles & Huberman through the 3 stages of the analysis process, namely the reduction of the Data, the presentation of the Data and Conclusions of withdrawal or verfikasi.